PENINGKATAN PEMBELAJARAN INOVATIF BERBASIS LITERASI DAN NUMERASI DI SD SIMBOLON PURBA KABUPATEN SAMOSIR - Tambunan, Formaida; Ria Royentina Sidabukke, Ida; Silitonga, Erwin (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The quality of education is one of the benchmarks for the success of a nation in giving birth to superior human resources by developing education through curriculum reform, development of teaching materials, character enhancement especially in terms of literacy and numeracy, which was initiated through the School Literacy Movement (GLS) in 2013. 2015. This movement aims to increase interest in reading and writing with literacy activities for 15 minutes before learning begins. The importance of literacy activities is to equip students with basic abilities to think critically and develop student competencies. To realize this government program, Sari Mutiara Indonesia University also supports in increasing literacy and numeracy skills through the Tri Dharma of Higher Education, which includes community service activities at SDN 11 Simbolon Purba. This activity gives positive results to the students by increasing the desire of the students to read in order to be able to understand any knowledge obtained from the teachers.